Closed loop small bowel occlusion through a congenital defect of the greater omentum - B Coulier; B Vander Elst; F Pierard (Journal of the Belgian Society of Radiology, 2010)
An 80-year-old male was admitted with a 15-h history of persistent epigastric and peri umbilical pain. Pain had spontaneously appeared during night and awakened the patient. There was neither nausea nor vomiting. Physical examination revealed moderate epigastric and supraumbilical abdominal tenderness. The patient was without surgical antecedent.